Socioeconomic inequalities and non-communicable diseases in Serbia: national health survey - Radević, Svetlana; Radovanović, Snežana; Djonović, Nela; Simić Vukomanović, Ivana; Mihailović, Nataša; Janićijević, Katarina; Kocić, Sanja (Vojnosanitetski pregled, 2020)
Abstract Background/Aim. Non-communicable diseases (NCDs) are a major public health challenge worldwide. Although they are preventable, NCDs are the major global causes of morbidity and mortality, absenteeism, disability and premature death. The aim of this study was to examine socioeconomic inequalities in the prevalence of non-communicable diseases in Serbia. Methods. Data from the 2013 National Health Survey of the population of Serbia was used in this study. There were 13,765 adults interviewed, aged ≥ 20 years. We used multivariate logistic regression analyses with demographic and socioeconomic determinants of health as independent variables and prevalence of non-communicable diseases as a dependent variable. The minimum level of significance was p < 0.05. Results. Hypertension was the most prevalent NCDs (36.1%). The prevalence of multimorbidity was 47.1%. Multivariate logistic regression analysis showed that gender, age, place of residence, employment status and education were associated with the presence of NCDs.  The odds ratio (OR) for age was 1.074 [95% confidence interval (CI) : 1.070–1.077). Women were at a higher risk of NCDs by 58.9% when compared to men (OR = 1.589; 95% 95% CI : 1.467–1.726). Respondents who lived in the rural areas were at a higher risk for NCDs by 14.1% compared to those who lived in urban areas (OR = 1.141; 95% CI : 1.047–1.244). Odds ratio for unemployment was 1.227 (95% CI: 1.118–1.346). Respondents with primary education were at a higher risk for chronic diseases by 47.1% (OR = 1.471; 95% CI : 1.281–1.687) while those with secondary school were at a higher risk  by 27.7% (OR = 1.277; 95% CI : 1.142–1.428) compared to respondents who had higher education. When it comes to Wealth Index, univariate logistic regression analysis showed that respondents who belonged to the poor and middle classes were at a higher risk for NCDs (OR = 2.031; 95% CI : 1.819–2.267;  OR = 1.473; 95% CI : 1.343–1.615) compared to respondents who belonged to the rich class. Multivariate logistic regression analysis did not show statistically significant correlations between the Wealth index and NCDs. Conclusion. Socioeconomic inequalities in health status are the major challenge and should be a target of national health policy in Serbia, not only because they represent social injustice but also because solving the health problems of underprivileged groups of the population can influence improvement of health status of the population as a whole.
Keywords: chronic disease; prevalence; risk factors; sociological factors; economics; serbia.